HUBUNGAN KESEIMBANGAN GERAK TERHADAP KETERAMPILAN BAKU TUNGGAL PERGURUAN HIMSSI KECAMATAN TAMBANG KABUPATEN KAMPAR - Azan Azwan; Agus Sulastio; Wedi S (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The purpose of this study is to find an explanation of the problemsstated above, namely to find out whether the relationship between movement balanceand single standard skills at the HIMSSI school in Tambang District, Kampar Regencyis very significant. This type of research is a correlational study. The results of the studyindicate that there is a significant relationship between Balance and Empty Hand SingleMoves, with a linear equation of Ŷ = 144.750 + 2.550X2 , correlation coefficient ry2 =0.590 and coefficient of determination (ry2 2) = 0.348, which means that the Balancevariable contributes to Empty Hand Single Moves by 34.8%. Correlation research isresearch conducted to determine whether there is a relationship between two or morevariables. This study was conducted to determine the relationship between MovementBalance and Single Standard Skills at the HIMSSI school in Tambang District, KamparRegency.Key Words: Balance of Movement, Single Standard Skill